Economic viability of Integrated Agricultural Production Systems From consortiums in the pasture phase in Mato Grosso, Brazil - Monteiro de Araujo Souza, Sandra Maria; Gomes, Aguinaldo Rocha; Sabbag, Omar Jorge [UNESP]; Pacheco, Leandro Pereira; Wruck, Flavio de Jesus; Wingert, Gustavo; Bau Macedo, Luis Otavio; Silva, Laercio Santos; Souza, Edicarlos Damacena de (Univ Fed Rural Pernambuco, Dept Administracao, 2023)
The particularities of Integrated Agricultural Production Systems (SIPA) influence implementation costs and production profitability. However, there are few scientific approaches that seek to elucidate the total cost of SIPA to assist in decision-making regarding the most appropriate modality to be installed. The purpose of the study was to propose the application of the appropriate costing method to SIPA for an integrated assessment of the economic and financial viability of SIPA with single and intercropped pastures under direct planting in Mato Grosso. Between 2015 and 2017, four types of SIPA in the pasture phase were evaluated for economic viability. Based on the cash flow, economic viability indicators were calculated: Net Present Value (NPV), Benefit/Cost Index (IBC) and Internal Rate of Return (IRR). The absorption costing method allowed a comprehensive assessment of SIPA production costs, and through the apportionment criterion, indirect costs were integrated into all production activities. SIPA have different levels of profitability, depending on the grass and the intercrop used. The overall net results in the 15/16 and 16/17 harvests ranged from R$ 701.81 to 1,889.01 in single pastures and from 1,435.86 to 2,129.39 in intercropped pastures. The systems showed the capacity to remunerate investments, especially when using Piata grass or a consortium between grasses and legumes with better economic indicators.
Keywords: Thick. Agricultural Credit. SIPA.